Prey Selectivity in Juvenile Red King Crabs from the Coastal Barents Sea - Lyudmila V. Pavlova; Alexander G. Dvoretsky (Diversity, 2022)
The invasive red king crab, Paralithodes camtschaticus, has become an abundant and important component in the food web of the coastal Barents Sea and can affect the structure and functioning of the local benthic communities through competition and predation. Although dietary composition and feeding behavior of the crab have been intensively studied, prey selectivity in this species under natural conditions remains poorly defined. For this reason, juvenile red king crabs and benthic samples were collected simultaneously at five coastal sites in Kola Bay to reveal the species composition and structure of feeding habits and the diet of red king crabs. The results of stomach and gut content analyses coupled with calculated Ivlev’s indices indicated that 2–5-year-old crabs frequently consumed bivalve mollusks in relative proportions to prey field biomasses. At all sites, juveniles selectively rejected polychaetes. In soft-bottom communities, when the average density of Bivalvia decreased, the crabs showed increased preference for Gastropoda, Crustacea, and Echinodermata. As a result of selective feeding focused on infaunal suspension-feeding mollusks, juvenile red king crabs have altered the structure of benthic communities in the mouth of Kola Bay. Our results may have important implications for evaluating the consequences of the crab introduction and its population management.